EDUKASI DAN DEMOSTRASI PEMBUATAN "PUDING PELOR" (KELOR TEMPE) DALAM UPAYA PENCEGAHAN STUNTING - Sofiyatin, Reni; Panduwinata, Fina; Rizka Dila Andini; Nadiya Rizqayana Dimiyati; Adinda Vira Anjani (Jurnal Pengabdian Masyarakat Sasambo, 2025)
Stunting in toddlers occurs starting when the baby is still in the mother's womb, then the symptoms of stunting will begin to appear when the age of the toddler has reached 24 months. The stunting process can have a serious impact if it occurs during the golden age period of child brain development. to prevent stunting in children, it is necessary to provide health education about stunting and nutritious food demonstrations. The purpose of this activity is to introduce healthy snacks with high nutrition for stunting prevention. Methods: Lecture with leafleat media and demonstration of making moringa tempeh pudding “ Puding Pelor” , evaluation of the acceptability of moringa tempeh pudding in toddlers. Results:  Moringa tempeh pudding yields nutritional values in 1 serving (30 grams) Energy: 119.1 kcal, Protein: 7.32 g, Fat: 3.08 g, Carbohydrate: 17.3 g and 100% acceptability in the Good category, so that tempeh moringa pudding can be recommended as a healthy snack for children under five in the prevention of stunting.